Desain dan Implementasi Modul Kit Laboratorium Mikrokontroler AT89S52 dengan Single PCB, Portable dan Prospektif - Milda Yuliza; Fatum Rahmana Putra; Yultrisna Yultrisna; Era Madona; Adi Chandranata (Manutech : Jurnal Teknologi Manufaktur, 2023)
This study aims to design and implement a new design of a single PCB, portable and prospective laboratory kit module. The laboratory kits made are easy to assemble, with relatively small dimensions. and suitable for use in laboratories with limited experimental space and funds. The objectives of this research are (a) creating a microcontroller trainer by creating a series of minimum systems, inputs, outputs, Analog Digital Converter (ADC), (b) system programming using the Keil C51 IDE, (c) measuring and testing trainer performance. The research method starts from making a physical trainer, programming the microcontroller and measuring circuit performance. Pulse width modulation (PWM) of DC motors and the direction of rotation of the motor can be controlled using a potentiometer. The wave that is obtained when the motor is at full speed is in the form of a straight line with a voltage of 9.12 V, while when the motor is at half-full speed, a PWM pulse wave is obtained with a voltage of 4.35 V. The test is carried out based on student practicum work on each input circuit, and the output results are all applications tested successfully as expected.